Research Ethics Oversight for Multi-jurisdictional Clinical Trials in Canada: A Historical Perspective to Inform Future Direction - Lucas, Brenda; Flamenbaum, Jaime; Longstaff, Holly; Murthy, Srinivas; Schichter, Brittney (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2024)
As a condition of funding from the Canadian Tri-Agencies, researchers and institutions are expected to adhere to the Tri-Council Policy Statement: Ethical Conduct for Research Involving Humans (TCPS) and research projects must obtain approval from a Research Ethics Board (REB). Yet there are a limited number of frameworks and standards to guide the conduct and decisions of REBs in Canada and these are most often voluntary. Delays and increased costs resulting from the lack of a common or coordinated approach to REB review for multi-jurisdictional clinical trials is a long-standing issue in the Canadian research environment. Formal reviews and recommendations as early as 2006 call for accreditation or qualification for REBs, use of common forms and templates, and federal leadership to harmonize processes.